2009
DOI: 10.1515/cclm.2009.272
|View full text |Cite
|
Sign up to set email alerts
|

Error tracking in a clinical biochemistry laboratory

Abstract: Background: We report our results for the systematic recording of all errors in a standard clinical laboratory over a 1-year period. Methods: Recording was performed using a commercial database program. All individuals in the laboratory were allowed to report errors. The testing processes were classified according to function, and errors were classified as pre-analytical, analytical, post-analytical, or service-related, and then further divided into descriptive subgroups. Samples were taken from hospital wards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 17 publications
4
26
0
1
Order By: Relevance
“…There has been varied information on error rate within whole lab testing procedure (0.1-9.3%). 7 Our study is in accordance with Pleboni and Carroro who in their research also observed that majority of errors in laboratory results due to the problem in pre-analytical phase.…”
Section: Discussionsupporting
confidence: 92%
“…There has been varied information on error rate within whole lab testing procedure (0.1-9.3%). 7 Our study is in accordance with Pleboni and Carroro who in their research also observed that majority of errors in laboratory results due to the problem in pre-analytical phase.…”
Section: Discussionsupporting
confidence: 92%
“…Although several articles have described preanalytic errors in terms of unacceptable samples, such as hemolysed, clotted, and/or insufficient specimens (4,5,(7)(8)(9), few data available in the literature relate this type of quality failure to mechanisms and procedures which, if not followed, expose patients to the risk of errors and the related adverse events, particularly in the case of patient misidentification. The data reported in the present study confirm the relative frequency of prepreanalytic errors, including the misidentification error rates, found to be 359 parts per million (ppm), a rate that is similar to that previously reported (270 ppm) (5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of pre-analytical factors of variation is very high as published and itemized by Young (2007). According to estimations in human laboratory diagnostics, the lack of standardized procedures in specimen acquisition, handling and storage account for the majority of all errors currently encountered within the entire diagnostic process (Lippi et al, 2006a;Wallin et al, 2008;Szecsi and Odum, 2009;Goswami et al, 2010).…”
Section: Introductionmentioning
confidence: 99%